(untitled) (Scientific journal of the Fergana State University, 2023)
Studies have been carried out to obtain complex fertilizers based on suprefos pulp, NH4NO3 and KCl at pH = 5.25 and 60°С and mixing time of 120 min. As a result of granulation and drying, high-quality complex fertilizers were obtained with a content of 17.76% SO3, 18.71% N; 18.88%, 17.08% SO3, 7.02% N; 18.53% Р2О5tot.; 18.42% K2O and 14.34% N; 13.91% Р2О5tot.; 13.81% K2O, 12.98% SO3, corresponding to grades N : P = 1 : 1, N : P : K = 0.4 : 1 : 1 and 1 : 1 : 1 with a high degree of conversion equal to 93.66 ; 97.78 and 99.61%. Judging by the content of SO3 in the range of 12.98-17.76%, they can also be called NPS- and NPKS-fertilizers. The salt composition was studied by radiography, in which dicalcium phosphate, nitrate, sulfate and phosphate of ammonium and potassium were found.